Examination of Sustainability Strategies of Enterprises that Operate in the Sports Industry - Arif Yüce; Sevda Gökce Yüce; Hakan Katırcı (Universitas Pasundan, 2020)
The concept of sustainable production/consumption is one of the key points that need to be addressed in terms of measures and alternatives. As one of the most important industries today, the sports industry appeals to a wide range of consumers through various goods and services offered to consumers. The present view is that it is important to look out for sustainable production/consumption and to implement sustainability strategies both in terms of enterprises and of products and services offered to consumers. In this context, the main purpose of this study is to describe and examine the sustainability strategies of enterprises that produce goods and services in the sports sector. Within the scope of this inquiry, this study utilized the qualitative research technique of semi-structured interviewing. The interviews with senior managers in the sports sector were conducted in the Turkish city of Eskişehir. The results showed that the awareness levels of the companies regarding sustainability are lacking and that the corresponding strategies implemented were also insufficient.